Hematopoietic Stem and Immune Cells in Chronic HIV Infection - Jielin Zhang; Clyde Crumpacker (Stem Cells International)
Hematopoietic stem cell (HSC) belongs to multipotent adult somatic stem cells. A single HSC can reconstitute the entire blood system via self-renewal, differentiation into all lineages of blood cells, and replenishment of cells lost due to attrition or disease in a person’s lifetime. Although all blood and immune cells derive from HSC, immune cells, specifically immune memory cells, have the properties of HSC on self-renewal and differentiation into lineage effector cells responding to the invading pathogens. Moreover, the interplay between immune memory cell and viral pathogen determines the course of a viral infection. Here, we state our point of view on the role of blood stem and progenitor cell in chronic HIV infection, with a focus on memory CD4 T-cell in the context of HIV/AIDS eradication and cure.